O direito à moradia e o bem de família: inconstitucionalidade do inciso VII, art. 3º, Lei nº 8.009/90 - Falsoni, Susana Ferreira (2009)
The objective of this present work is the analysis of the unconstitutionality of the article 3o, incise VII, of the Law 8009/90, that brings as an exception to the rule of the impossibility of seizing a freehold estate the cases of debts derived from bails given in location contracts, even though the surety complies with the conditions to take advantage of the general rule of the impossibility of seizing, that are: to be an owner of only one property and this property is his own or is his family s residency. In order to clarify it, we will talk about the historical context that the Country was living when the edition not only of the referred Law 8009/90 but also of the Tenant s Law that added the incise VII to the article 3o, specific object of this study, besides approaching themes like right to equality, fundamental rights, collision among fundamental rights, juridical institutions, among others